2020
DOI: 10.1177/2192568220921833
|View full text |Cite
|
Sign up to set email alerts
|

Does L5-S1 Anterior Lumbar Interbody Fusion Improve Sagittal Alignment or Fusion Rates in Long Segment Fusion for Adult Spinal Deformity?

Abstract: Study Design: Retrospective cohort study. Objectives: To assess whether the addition of L5-S1 anterior lumbar interbody fusion (ALIF) improves global sagittal alignment and fusion rates in patients undergoing multilevel spinal deformity surgery. Methods: Two-year radiographic outcomes, including lumbar lordosis, pelvic incidence, pelvic tilt, and T1 pelvic angle; hardware complications; and nonunion/pseudarthrosis rates were compared between patients who underwent lumbosacral fusion at 4 or more vertebral leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Multiple longitudinal studies with at least 2-year follow-ups have demonstrated that there is a loss of the initial correction in LL. 7,8 Although these studies did not specifically look for loss of correction as an outcome of interest, their data consistently showed an average decrease in LL of ~5 degrees. Importantly, this expected change should not be taken as a reason to "overcorrect" patients at the time of surgery, especially considering that PROs were comparable between the M and L cohorts.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple longitudinal studies with at least 2-year follow-ups have demonstrated that there is a loss of the initial correction in LL. 7,8 Although these studies did not specifically look for loss of correction as an outcome of interest, their data consistently showed an average decrease in LL of ~5 degrees. Importantly, this expected change should not be taken as a reason to "overcorrect" patients at the time of surgery, especially considering that PROs were comparable between the M and L cohorts.…”
Section: Discussionmentioning
confidence: 98%
“…While this does not seem to make intuitive sense, past investigations on L5-S1 IBFs in long constructs have demonstrated similar findings. 7,23 In contrast to 1-2 level fusions, IBF may not impart as much mechanical stability in longer constructs due to how stress is distributed over a larger area. 24 This proposed concept is similar to the use of lag screws for simple oblique fractures versus long bridge plates for comminuted fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ALP, carboxyterminal telopeptide end of type 1 collagen (CTX), BGP, and P1NP were used to evaluate the effect of ONO‐5334 and teriparatide in treating postmenopausal osteoporosis 21,22 ; CT and PTH can also affect bone mineral density in patients, 23,24 and 25OH vitamin D with calcium and phosphorus were found to affect bone density and bone strength not only in healthy adults 25 but also in patients who have undergone gastric bypass surgery 26 or kidney transplantation 27 . Moreover, some studies have found that preoperative radiographic indicators, including sagittal alignment and segmental motion, could affect cervical or lumbar fusion after ACDF or anterior lumbar interbody fusion 18,28 . However, the association between bone turnover markers, hormone levels associated with bone metabolism, 25OH vitamin D with calcium and phosphorus, and preoperative radiographic indicators and early cervical fusion rates remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Baldairon et al (14) found that supine MRI was a valid alternative to standing x-rays for measuring upper thoracic kyphosis in the sagittal plane. However, the efficacy of x-ray and MRI in evaluating spinal sagittal alignment in DLD is controversial (15,16), and further studies are needed to evaluate their effectiveness.…”
Section: Introductionmentioning
confidence: 99%